Leveraging Artificial Intelligence for Enhanced Data Security Measures - Pal, Prabhakar (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2024)
In today’s highly digital world, where everything is interconnected, keeping important information safe from new cyber dangers is important. The usual ways we use to protect data are not as effective because the threats are getting more advanced. This study investigates how AI can be used alongside security systems to make them stronger and reduce the chances of cyberattacks causing harm. The paper starts by looking back at how cyber threats have changed over time. It shows how the usual ways we used to protect against these threats are not enough anymore. Then, it talks about how AI, like machine learning and other AI technologies, can help make our data safer. It explains how AI can do things like spot unusual activity, predict threats, and keep data secret. This shows how AI can help find and stop problems before they become big issues. The article shows real benefits and demonstrates how AI-integrated security systems can make data protection stronger. Addressing concerns of privacy violations, algorithmic bias, and responsible AI deployment, this paper navigates the ethical contours of leveraging AI for safeguarding sensitive information, underscoring the imperative of ethical guidelines in technological advancements. Drawing insights from practical implementations and successful case studies across industries such as finance, healthcare, and e-commerce, the article shows real benefits and demonstrates how AI-integrated security systems can make data protection stronger. Moreover, the paper forecasts future trajectories, emphasising the need for continual innovation, interdisciplinary collaborations, and ethical frameworks to steer the evolution of AI-driven data security. It finishes by saying how AI can really make data security stronger. It understands that there are moral, practical, and future aspects that affect how AI and cybersecurity work together as things keep changing